Jharkhand matters: essays on ethnicity, regionalism, and development - Balakrishnan, Rajiv.; Council for Social Development (India) (Konark Publishers, 2004)
On economic and political conditions of Jharkhand; contributed articles.
"In association with Council for Social Development, New Delhi."
Includes bibliographical references and index.
On economic and political conditions of Jharkhand; contributed articles.
Keywords: Jharkhand (India) / Politics and government.; Jharkhand (India) / Economic conditions.